2004
DOI: 10.1080/13645700310022691
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive probe system capable of performing both cryosurgery and hyperthermia treatment on target tumor in deep tissues

Abstract: Cryosurgery is a clinical therapy aiming at the destruction of diseased target tissues through a controlled deep freezing and subsequent rewarming. It has recently been realized that freezing immediately followed by a rapid and strong heating of the target tissues would significantly improve the treatment effect. However, most of the currently available cryoprobe systems are only capable of performing a single freezing function. To accommodate to the rapid growth of the combined freezing and heating therapy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…Later, Hines-Peralta et al 32 proposed a hybrid device to enhance the efficiency of a bipolar RF system by placing a freezing unit between the two RF poles. Liu et al 33 designed a cryo-probe system with vapour heating, and found that freezing -…”
Section: Discussionmentioning
confidence: 99%
“…Later, Hines-Peralta et al 32 proposed a hybrid device to enhance the efficiency of a bipolar RF system by placing a freezing unit between the two RF poles. Liu et al 33 designed a cryo-probe system with vapour heating, and found that freezing -…”
Section: Discussionmentioning
confidence: 99%
“…Recently, freezing and heating have been combined to improve output of tumor treatment [16][17][18][19][20]. As far as heating intensity is concerned, typical representatives of freezing-heating systems are cryoprobe-apparatus with internally circulated high-velocity fluids (deep low-temperature liquid nitrogen and high-temperature water vapor) designed by Liu's group [19] and a similar freezing system but with radiofrequency heating from Xu's group [16].…”
Section: Introductionmentioning
confidence: 99%
“…As far as heating intensity is concerned, typical representatives of freezing-heating systems are cryoprobe-apparatus with internally circulated high-velocity fluids (deep low-temperature liquid nitrogen and high-temperature water vapor) designed by Liu's group [19] and a similar freezing system but with radiofrequency heating from Xu's group [16]. Researches have indicated that freezing immediately followed by a rapid and strong heating of the target tissues can effectively improve the ablation effects [16,19,21]. In addition, an induced larger thermal stress during AFH process also significantly enhances mechanical injury of tumor cell [19] and microvasculature [21].…”
Section: Introductionmentioning
confidence: 99%
“…Post histological analysis showed a good correlation between the vascular stasis and tissue necrosis, but no significant difference found in the size of the damaged tissue region as compared to that treated by cryosurgery or hyperthermia alone. Liu et al 33 investigated a new cryo-probe system with combined freezing and heating function through experimental studies in in vitro tissues and normal rabbits. Transient thermal stresses were observed and coupled with the rapid change of tissue temperature from freezing to heating, and the induced mechanical tissue damage was discussed.…”
Section: Introductionmentioning
confidence: 99%